2019
DOI: 10.1371/journal.pone.0218990
|View full text |Cite
|
Sign up to set email alerts
|

Clonally expanded alpha-chain T-cell receptor (TCR) transcripts are present in aneurysmal lesions of patients with Abdominal Aortic Aneurysm (AAA)

Abstract: Abdominal aortic aneurysm (AAA) is a life-threatening immunological disease responsible for 1 to 2% of all deaths in 65 year old or older individuals. Although mononuclear cell infiltrates have been demonstrated in AAA lesions and autoimmunity may be responsible for the initiation and account for the propagation of the disease, the information available about the pathogenesis of AAA is limited. To examine whether AAA lesions from patients with AAA contain clonally expanded α-chain TCR transcripts, we amplified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 90 publications
(176 reference statements)
0
9
0
Order By: Relevance
“…In addition to macrophages, clonal expansion of infiltrated T cells was suggested in the pathological areas of aortic wall in AAA. 32,33 Participation of immune cells has been studied also in TAA. Li et al 24 identified a higher proportion of T-lymphocytes in TAA than control aorta.…”
Section: Immune Cellsmentioning
confidence: 99%
“…In addition to macrophages, clonal expansion of infiltrated T cells was suggested in the pathological areas of aortic wall in AAA. 32,33 Participation of immune cells has been studied also in TAA. Li et al 24 identified a higher proportion of T-lymphocytes in TAA than control aorta.…”
Section: Immune Cellsmentioning
confidence: 99%
“…An AAA is now thought to result from a synergism between systemic immune imbalance and local autoimmunity [ 11 , 14 ]. The data published to date provide evidence that AAA is specific antigen-driven T-cell autoimmune disease [ 15 ]. Several autoantigens have been suggested to be involved in the development of AAA, among them collagen, elastin and fibrinogen [ 11 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that aortic damage and autoantigen exposure further contribute to the tissue destruction [ 11 ]. The inflammatory infiltrate in the AAA wall contains immunoglobulins, cytokines and proteases, all factors that implicate the activation of host innate and adaptive immune responses [ 11 , 12 , 13 , 14 , 15 , 16 ]. Considerable research has provided strong evidence that autoimmune processes are involved in the development of the AAA and contribute to the progressive degradation of the aorta [ 11 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, TCRs were analyzed in aortic aneurysms and their function has been investigated in mice and humans, yet no study addressed B cell clonality in aortic aneurysms. Li et al found clonal expansion of regulatory T cells (Treg) in mouse aortae after elastase-induced AAA formation [26] and several studies showed the presence of clonally expanded TCRs in aneurysmal lesions of patients with AAA or ascending thoracic aortic aneurysms, supporting the notion that AAA may be promoted by specific-antigen driven T cells [13,[27][28][29].…”
Section: Introductionmentioning
confidence: 92%